Free volume, thermal and morphological properties of photo-crosslinked thiol-Ene/nanodiamond hybrid network - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The purpose of this research paper is to investigate the changes in free volume by adding acrylate modified nanodiamond particles. In this study, a cross-linked thiol-ene (T) network was obtained under ultraviole light. The changes in free volume were analyzed when acrylate-modified nanodiamond (M-ND) particles were added to the nanocomposites obtained. Positron annihilation lifetime spectroscopy (PALS), a well-established method, was used for this analysis. In addition, the effect of nanocomposites containing different ratios of acrylate M-ND particles (1, 2, 3 and 5 Wt. %) on the surface and the thermal properties were also examined. Design/methodology/approach The impact of different quantities of acrylate M-ND on the free volume and surface morphological properties of thiol-ene polymer networks were studied by using scanning electron microscopy, differential scanning calorimetry, attenuated total reflection, Fourier transform infrared spectroscopy, PALS and thermogravimetric analysis measurements. Findings The thermal properties of T/M-ND were found to depend on the weight percentages of the M-ND content. For increasing weight percentages of M-ND added to thio-lene polymer networks, the glass transition temperature (T-g) increased from 103 degrees C to 154 degrees C. The ortho-positronium (o-Ps) lifetime (free volume) and free volume fraction characterization of T/M-ND nanocomposites were investigated using PALS. Increasing temperature caused both the o-Ps lifetime (free volume) to change with increasing saturation and to linearly increase the intensity; however, an increasing weight percentage of M-ND caused no change at all for the o-Ps lifetime (free volume) and the free volume fraction. Originality/value According to published literature, and to the best of the authors' knowledge, this is the first time a study examining the free volume properties in a thiol-ene system has been carried out.
Keywords: Free volume; Free volume fraction; Positron annihilation lifetime spectroscopy; Thiol-ene click reactions; POSITRON-ANNIHILATION; CONDUCTIVITY; NANODIAMOND; DEPENDENCE; POLYURETHANE; TEMPERATURE; POLYMERS; COATINGS; BEHAVIOR; SURFACE